Pengaruh Disiplin Kerja dan Lingkungan Kerja Terhadap Kinerja Karyawan pada Kantor Pendidikan Diklat Damkar Provinsi DKI Jakarta - Ayu Ritma Ratri; Ratnawati Marginingsih (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
The DKI Jakarta Provincial Fire and Rescue Training Education Office is a government building that serves the community in the field of fire prevention and control. One thing that is done is through discipline and the work environment for employees. This research aims to determine the influence of Work Discipline and Work Environment on Employee Performance at DKI Jakarta Province Fire and Rescue Education and Training Office companies. The research method used is a quantitative method approach with data collection techniques using a total sample or non-probability sampling where the entire population is sampled. The population in question is all employees of the civil service division of the DKI Jakarta Province Fire and Rescue Training Education office, totaling 40 respondents. This research instrument uses a questionnaire to collect data in Likert scale units. In managing data for analysis using the SPSS 20 application with multiple linear regression analysis techniques, the results of multiple linear regression analysis show that Y = 0.894, calculated 8.136 for the variable (X1), and 2.230 for the variable (X2), simultaneously the two independent variables obtained obtained an F count of 53.928. Based on the coefficient of determination test, it was found that the two independent variables had a 74.5% influence on employee performance.